Didactic bibliotherapy for character and moral development: A systematic review - Agustina, Susanti; Linda Setiawati; Johan, Riche Cynthia; Angga Hadiapurwa (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: Awareness of the importance of psychological well-being and personal growth progressively leads to the use of bibliotherapy in education, libraries, and psychology in all age groups. However, the lack of understanding of how to select and determine the right reading materials for each different age group in the context of bibliotherapy remains a challenge that needs to be addressed. Purpose: This study aims to explore the method of analyzing the content of certain books or literature in personal growth and motivation through didactic bibliotherapy. Methods: A systematic literature review (SLR) of various studies was conducted using the PRISMA framework. The review includes the selection and evaluation of bibliotherapy reading materials based on their didactic values and techniques, including character reflection, moral conflict resolution, and narrative structure. Findings: This review clarifies that didactic content analysis is essential for improving the educational and therapeutic impact of bibliotherapy. It identifies key didactic principles such as relevance to personal experiences, emotional engagement through relatable characters, and reflective narrative techniques. Conclusion: When combined with strong didactic principles, structured reflective approaches, and problem-solving techniques, bibliotherapy can make a significant contribution to psychological therapy and educational contexts by promoting self-reflection, problem-solving skills, and emotional management.